2018
DOI: 10.1007/s10787-018-0497-6
|View full text |Cite
|
Sign up to set email alerts
|

Nyctanthes arbor-tristis leaf extract ameliorates hyperlipidemia- and hyperglycemia-associated nephrotoxicity by improving anti-oxidant and anti-inflammatory status in high-fat diet–streptozotocin-induced diabetic rats

Abstract: Type 2 diabetes is a multifactorial disorder coupled with impaired glucose tolerance, diminished insulin sensitivity and hyperlipidemia. Incessant hyperglycemia and hyperlipidemia led a towering risk to develop cardiovascular hitches with end-stage renal failure. Leaves of Nyctanthes arbor-tristis L. (NAT) (family: Oleaceae) is traditionally used by tribes of Assam for various ailments without proper scientific validation and appropriate mechanism of action for its activity. Hence, we aimed to evaluate the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…As an efficient anti-inflammatory cytokine, IL-10 can improve hyperglycemia, and insulin resistance (51). NF-κB signaling is exacerbated in the glomeruli and renal tubes in patients with DN, and regulates the expression of inflammatory mediators and proinflammatory cytokines (10, 52). Hyperglycemia in diabetes leads to the activation of PKC, which further enhances the activation of NF-κB (53).…”
Section: Discussionmentioning
confidence: 99%
“…As an efficient anti-inflammatory cytokine, IL-10 can improve hyperglycemia, and insulin resistance (51). NF-κB signaling is exacerbated in the glomeruli and renal tubes in patients with DN, and regulates the expression of inflammatory mediators and proinflammatory cytokines (10, 52). Hyperglycemia in diabetes leads to the activation of PKC, which further enhances the activation of NF-κB (53).…”
Section: Discussionmentioning
confidence: 99%
“…The conflict between our research and previous studies possibly were attributed to the different ways of modeling. Diabetes was featured by hyperglycemia and hyperlipidemia co-occurred in the DN model of our study 33. Previous studies showed that high lipotoxicity was engaged in the occurrence and development of diabetic nephropathy 21,3437.…”
Section: Discussionmentioning
confidence: 51%
“…The results were calculated as nanomoles of GSH per milligram of protein. 54,55 4.16.3. Determination of Superoxide Dismutase (SOD) and Catalase (CAT) Activity.…”
Section: Methodsmentioning
confidence: 99%
“…Final absorbance was taken at 412 nm on a multiplate reader (SpectraMax i3x, Molecular Devices). The results were calculated as nanomoles of GSH per milligram of protein. , …”
Section: Methodsmentioning
confidence: 99%